Face-to-Face, or Face-to-Visor. Is Cinematic Virtual Reality the “Ultimate Empathy Machine”? - Rainoldi, Giulia (Bollettino Filosofico, 2022)
My paper makes a comparison between one possible definition of empathy and the spectator’s experience in VR with the aim of assessing whether these two structures are compatible in a more rigorous way. Following the phenomenological works of Maurice Merleau-Ponty and Vittorio Gallese’s writings on embodied simulation, I will define empathy in the VR context as the result of four different conditions: 1) the VR user and the VR character must share the same ontological structure, for the other is a “second self”, therefore 2) the character must be directly accessible in an intersubjective and reversible relation. Furthermore, 3) it is necessary for the VR user to understand the object of the character’s emotion to strengthen the empathetic response provided by the embodied simulation, but 4) this does not ever mean that empathy leads to a total correspondence of state of minds, as the character’s suffering is always different from what the spectator feels while seeing that suffering. Taking these four conditions in mind, I then apply them to the analysis of the VR documentary Clouds over Sidra (Milk, Arora, 2017), which follows the story of Sidra, a refugee child displaced in the Za’atari refugee camp. My conclusion is that VR engenders an occasion of emotional contagion, which is the quite literal infection of the character’s feeling to the VR user. Keywords: Embodied Simulation, Emotional Contagion, Intersubjective Relation, Phenomenology, Virtual Reality